Neonatal deaths in infants born weighing ≥ 2500 g in low and middle-income countries - Sarah Saleem; Farnaz Naqvi; Elizabeth M. McClure; Kayla J. Nowak; Shiyam Sunder Tikmani; Ana L. Garces; Patricia L. Hibberd; Janet L. Moore; Tracy L. Nolen; Shivaprasad S. Goudar; Yogesh Kumar; Fabian Esamai; et al. (BMC, 2020)
Abstract Background Babies born weighing ≥ 2500 g account for more than 80% of the births in most resource-limited locations and for nearly 50% of the 28-day neonatal deaths. In contrast, in high-resource settings, 28-day neonatal mortality among this group represents only a small fraction of the neonatal deaths. Yet mortality risks for birth weight of ≥ 2500 g is limited. Knowledge regarding the factors associated with mortality in these babies will help in identifying interventions that can reduce mortality. Methods The Global Network's Maternal Newborn Health Registry (MNHR) is a prospective, population-based observational study that includes all pregnant women and their pregnancy outcomes in defined geographic communities that has been conducted in research sites in six low-middle income countries (India, Pakistan, Democratic Republic of Congo, Guatemala, Kenya and Zambia). Study staff enroll all pregnant women as early as possible during pregnancy and conduct follow-up visits to ascertain delivery and 28-day neonatal outcomes. We analyzed the neonatal mortality rates (NMR) and risk factors for deaths by 28 days among all live-born babies with a birthweight ≥ 2500 g from 2010 to 2018 across the Global Network sites. Results Babies born in the Global Network sites from 2010 to 2018 with a birthweight ≥ 2500 g accounted for 84.8% of the births and 45.4% of the 28-day neonatal deaths. Among this group, the overall NMR was 13.1/1000 live births. The overall 28-day NMR for ongoing clusters was highest in Pakistan (29.7/1000 live births) and lowest in the Zambian/Kenyan sites (9.3/1000) for ≥ 2500 g infants. ≥ 2500 g NMRs declined for Zambia/Kenya and India. For Pakistan and Guatemala, the NMR remained almost unchanged over the period. The ≥ 2500 g risks related to maternal, delivery and newborn characteristics varied by site. Maternal factors that increased risk and were common for all sites included nulliparity, hypertensive disease, previous stillbirth, maternal death, obstructed labor, severe postpartum hemorrhage, and abnormal fetal presentation. Neonatal characteristics including resuscitation, hospitalization, congenital anomalies and male sex, as well as lower gestational ages and birthweights were also associated with increased mortality. Conclusions Nearly half of neonatal deaths in the Global Network sites occurred in infants born weighing ≥ 2500 g. The NMR for those infants was 13.1 per 1000 live births, much higher than rates usually seen in high-income countries. The changes in NMR over time varied across the sites. Even among babies born ≥ 2500 g, lower gestational age and birthweight were largely associated with increased risk of mortality. Since many of these deaths should be preventable, attention to preventing mortality in these infants should have an important impact on overall NMR. Trial registration: https://ClinicalTrials.gov Identifier: NCT01073475